Using Mirror Patients to Enhance Patient Safety. Issue 3 (June 2019) - Harwayne-Gidansky, Ilana; Culver, Kathleen; Cavanaugh, Sean; Panesar, Rahul
Abstract : Summary Statement: Unannounced, in situ simulations offer opportunities for interprofessional teams to train for pediatric emergencies and uncover latent safety threats (LST). Simulation fidelity is an important component of in situ simulations. Threats to fidelity include creating a fictional patient vignette, which limits realism and the opportunity for patient handoffs. The "mirror patient" model may enhance in situ simulation fidelity by using actual patient profiles, thereby removing vignettes and allowing for handoffs. This model may also aid in discovering LSTs. The mirror patient was positively received by participants, who reported realistic and useful simulation experience that provided a safe and supportive learning environment. Uncovering, recording, and reviewing LSTs into an institutional safety event reporting system allowed for tracking and accountability, including process improvement, equipment changes, and provider training without risk to any real patient. This model may further improve means to enhance hospital patient safety. Abstract : Supplemental digital content is available in the text.